Crystallization behavior and soft magnetic properties of Fe–B–P–C–Cu ribbons with amorphous/α-Fe hierarchic structure. (April 2021) - Li, Yuluo; Shen, Ningning; Zhang, Suo; Wu, Yidong; Chen, Li; Lv, Kuang; He, Zhanbing; Li, Fushan; Hui, Xidong
Abstract: In this work, Fe83+ x (B4 P8 C4 )16- x Cu1 ( x  = 0, 1, 1.5 and 2 at. %) alloy system with amorphous/α-Fe hierarchic structures in as-cast state were artificially designed. The microstructure, crystallization kinetics, nanocrystalline structure, and magnetic properties of the alloys were systematically investigated. And the structural mechanism for the magnetic properties of these alloys was discussed. It is shown that the structure is evolved from full amorphous to amorphous/α-Fe dual-phase microstructure in the free surface side, and/or roller side layer with Fe content increasing. The formation of hierarchic structure decreases the activation energies of onset and peak crystallization of α-Fe phase, and increases the size of nanocrystalline grains, and subsequently is beneficial to improve the B s of alloys. The H c of alloys increases due to the formation of hierarchic structure, whereas this effect is gradually eliminated by the annealing process at the suitable crystallization annealing temperature ( T a ). Typically, Fe85 B3.5 P7 C3.5 Cu1 nanocrystalline alloy exhibit the B s of 1.86T and H c of 5.7 A/m after annealing at 723 K. High Fe bearing alloys have lath domain structure with stronger orientation preference in as-cast state, and transformed into labyrinth packing with thinner spacing after structural relaxation annealing, demonstrating that hierarchic structure leads to the high magnetic anisotropy in the alloys. Highlights: Magnetic properties of Fe–B–P–C–Cu alloys with hierarchic structure were studied. Adverse effect of hierarchic structure can be eliminated by crystallize annealing. Fe85 B3.5 P7 C3.5 Cu1 alloy annealed at 723 K exhibit B s of 1.86T and H c of 5.7 A/m.